Participatory vegetable and seed system development enabled ethnic minority farmers in Northern Vietnam to form local value chain networks and increase production 5-7-fold. - Swaans, Cornelis P.M.; Nabuuma, Deborah (2023)
Through participatory vegetable and seed system development, ethnic minority farmers in target sites were organized in value chain groups to jointly produce and market various vegetable seeds/seedlings and vegetables. With the support of project partner and local partners, the groups’ capacity to identify market opportunities and engage with value chain actors improved, whereby production increased by 5-7 times, from 70 to 400 tons after two years. Group and individual incomes also increased, and one group proceeded to register as a cooperative.